It takes a village... Program-wide approaches to redesigning assessment in a time of generative artificial intelligence (GenAI). - Nicola-Richmond, Kelli; Dawson, Phillip; Helen, Partridge; Macfarlane, Susie (Journal of University Teaching and Learning Practice, 2025)
The rapid maturation of generative artificial intelligence (GenAI) platforms has created significant challenges for higher education, particularly in relation to assessment. This project sought to explore the lived experiences and views of GenAI in relation to assessment for academics and students in higher education. A qualitative interpretivist approach was adopted, using semi-structured interviews.  When data were thematically analysed, three themes were developed; emotions, academic role and identity; assessment must change, and the work and expertise required to change assessment. Academics and students experienced both positive and negative emotions in relation to GenAI. Concerns about the complexity of changing assessment and resources needed to change assessment were pervasive. Based on these findings we propose that “it takes a village” to redevelop assessments in a time of GenAI and therefore collaborative, program-wide approaches are the way forward.